(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2011)
In information age, sending the data from one end to another endneed lot of space as well as time. Data compression is atechnique to compress the information source (e.g. a data file, aspeech signal, an image, or a video signal) in possible fewnumbers of bits. One of the major factors that influence the DataCompression technique is the procedure to encode the sourcedata and space required for encoded data. There are many datacompressions methods which are used for data compression andout of which Huffman is mostly used for same. Huffmanalgorithms have two ranges static as well as adaptive. StaticHuffman algorithm is a technique that encoded the data in twopasses. In first pass it requires to calculate the frequency of eachsymbol and in second pass it constructs the Huffman tree.Adaptive Huffman algorithm is expanded on Huffman algorithmthat constructs the Huffman tree but take more space than StaticHuffman algorithm. This paper introduces a new datacompression Algorithm which is based on Huffman coding. Thisalgorithm not only reduces the number of pass but also reducethe storage space in compare to adaptive Huffman algorithm andcomparable to static.